2017
DOI: 10.24200/sci.2017.4531
|View full text |Cite
|
Sign up to set email alerts
|

Study on wind-induced response of fluid-solid coupling system for high bent-type aqueduct

Abstract: Abstract. In this paper, the coupling responses of water and high bent-type aqueduct under wind loads were studied by the Arbitrary Lagrangian-Eulerian (ALE) method. The natural vibration characteristics and transversal displacement, stress, overturning force, overturning moment, and hydrodynamic pressure of water-aqueduct coupling system were comparatively analyzed under di erent conditions of water-depth, cross-section shape of aqueduct tank, and support bearing. The research results show that the isolated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…They demonstrated that the enlargement of the draft has been led to the increment of the angle of attack, the beam of the pressure source, and the height of the generated wave. Zhang et al [15] employed the Arbitrary Lagrangian-Eulerian (ALE) method to evaluate the coupling responses of water and aqueducts with high bent-type under wind loads. They proved that the isolated support altered the dynamic properties and reduced the wind resistance performance of the U-shape aqueduct.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the enlargement of the draft has been led to the increment of the angle of attack, the beam of the pressure source, and the height of the generated wave. Zhang et al [15] employed the Arbitrary Lagrangian-Eulerian (ALE) method to evaluate the coupling responses of water and aqueducts with high bent-type under wind loads. They proved that the isolated support altered the dynamic properties and reduced the wind resistance performance of the U-shape aqueduct.…”
Section: Introductionmentioning
confidence: 99%